Progress towards the innovation potential of the European union member states using grey relational analysis and multidimensional scaling methods - Tutak, Magdalena; Brodny, Jarosław (Decision Making: Applications in Management and Engineering, 2023)
The article presents the results of a study aimed at assessing the level of innovation potential of European Union member states. The research was based on 8 diagnostic variables characterizing the two most important dimensions of innovation, namely human resources and R&D expenditures. As a result of the research, the levels of innovation potential of European Union countries between 2010-2020 were specified. The GRA approach and multidimensional scaling were used for the study. Based on the results, the European Union countries were divided into 4 classes. The findings showed large differences in this potential across countries, which was graphically illustrated by using the multidimensional scaling method. In addition, using two non-parametric tests, (Spearman Rank Correlation Coefficient and Kendall Correlation Coefficient), relationships between the innovation potential of member states and selected economic and innovation parameters of their economies were determined. The results of the study indicate that in the old EU-14 countries, this level was at a significantly higher level than in the new EU-13 countries. The EU-27 innovation potential leaders were found to be Finland, Sweden, Luxembourg, Denmark, and Germany. The worst performers, on the other hand, are Malta and Romania. Also, geographically, there were noticeable differences between the countries studied. The results presented should be used to develop strategies and implement policies for sustainable innovative development in the European Union. To the best of the authors' knowledge, this study is a new contribution to assessing the level of innovation potential of European Union member countries and determining the relationship of this potential with selected parameters of the economy of these countries.